PEMBERDAYAAN KELOMPOK TANI MELALUI PASAR LELANG SEBAGAI SOLUSI MEWUJUDKAN KEDINAMISAN KESEJAHTERAAN PETANI - Adhi Surya Perdana (Universitas Tidar, 2016)
Empowerment research of farmer group through the auction market as an embodies solution of farmer dynamism welfare. The purpose research was to describe the characteristics farmers relationship through farmer group as empowerment approach, knowing the form empowerment farmer groups through the auction market, and the dynamism of farmers welfare. This research was conducted in the Bugel Village and Garongan was farmers group of Gisik Pranaji and Bangun Karyo. The research method was descriptive qualitative case study. The primary data collection was done by purposive sampling based on specific criteria, carried out using questionnaires, interview, direct observation group activities, and secondary data collection. The result of study said, relations characteristics farmer group empowerment approach through which their direct ownership farmer group empowerment approach and the growth of community building on every farmer who has a collectivity and social care. Proceeds from sale market activity which is the type Helix Rp.57.816.000,- and type Lado Rp.11.325.187,-. Profit received farmer groups reached Rp.1.081.500 plus the cost of energy service income, cash costs struggle and farmer groups Conslucions of research were the existence of integration between management and members of the group together with the market traders to determine base price of red chilli, with the support functions of the partnership market. The achievement dynamism of the farmer welfare, including the group’s goals, a sense of the relationship with the members of the others, the interaction of farmers who have a positive influence on group (living in harmony and peace), and realize the effectiveness of group toward partnerships benefit mutually farmers.